1995
DOI: 10.1002/mrdd.1410010209
|View full text |Cite
|
Sign up to set email alerts
|

Opiate mechanisms in self‐injury

Abstract: Self‐injuring behavior is among the most unmanageable, expensive, destructive, and unpredictable behaviors exhibited by human beings. Interventions that included punishment or restraint were among the most successful for acute control of SIB. Both painful shock and restraint stimulate release of the body's own opiates into the bloodstream. These powerful agents, which possess analgesic and addictive properties, are more potent than morphine. Based on these observations, two versions of the opiate hypothesis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 63 publications
3
45
0
1
Order By: Relevance
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals who repeatedly injure themselves appear immune to the normal experience of pain (Sandman & Hetrick, 1995). They employ an assortment of self-harmful methods that include cutting, hitting or biting themselves, hurling themselves to the ground and banging their head against solid objects resulting in broken bones, disfigurement, blindness and even loss of life (Claes & Vandereycken, 2007; Sandman, Spence, & Smith, 1999; Thompson, Hackenberg, Cerutti, Baker, & Axtell, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although the cause is unknown, contemporary studies suggest that a biological imbalance or defect is associated with SIB (Sandman et al, 1999; Sandman et al, 1995; Thompson et al, 1994; Chamberlain & Herman, 1990; Gillberg, 1995; Cazzullo, Musetti, Musetti, Bajo, Sacerdote, & Panerai, 1999; Lewis, Bodfish, Powell, Parker, & Golden, 1996). Evidence from several laboratories indicates that the processing and release of a stress-related molecule (proopiomelanocortin, POMC) in the hypothalamic-pituitary-adrenal (HPA) axis may be perturbed among subgroups of individuals exhibiting SIB (Sandman et al,1999; Sandman & et al,1995; Gillberg, 1995; Bouvard et al, 1995; Ernst et al, 1993; Leboyer et al, 1994; Leboyer et al, 1999; Sandman, Barron, Chicz-DeMet, & DeMet, 1990a; Sandman, Barron, DeMet, Chicz-DeMet, & Rothenburg, 1990b; Sandman, Hetrick, Taylor, & Chicz-DeMet, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two POMC or opiate hypotheses of SIB, increased pain tolerance and addiction to endogenous opioids, have been proposed [Sandman and Hetrick, 1995]. In studies by Sandman et al [1990Sandman et al [ , 1997 plasma levels of highly specific immunoreactive ␤-endorphin (␤) activity were elevated relative to the coreleased peptide, ACTH, minutes after an SIB episode.…”
Section: Opioids Addiction and Stress In The Maintenance Of Sibmentioning
confidence: 99%